Identification of BRCA1 tumor suppressor gene expression as a DNA repair gene in frozen cleavage embryo cell at IIUM Fertility Centre - Abdul Razak, Redzuan Nul Hakim; Abdul Wahab, Azantee Yazmie; Ramli, Roszaman; Nik Osman, Nik Mohammed Faez; Nik Hassan, Nik Fakhuruddin; Muhammad, Hussin; Mazlan, Muhammad Alif; Md Isa, Muhammad Lokman (Malaysian Society for Biochemistry and Molecular Biology, 2020)
BRCA1 is known as the essential tumor suppressor gene in human that expresses a protein that called breast cancer type 1 susceptibility protein. It has two main functions which are repairing the damaged DNA and also inducing the apoptotic mechanism to eliminate the cell when mutated DNA could not be repaired. In this study, all the embryo samples that have been used were considered as grade 1 according to Embryo Grading. This study aimed to investigate BRCA1 gene expression in relation to the human embryo quality. The RNA from the cleavage embryo was extracted and was tested by Reverse-Transcriptase Polymerase Chain Reaction (rt- PCR) and gel electrophoresis. The results showed that BRCA1 gene expression was expressed in frozen cleavage embryos. Furthermore, the statistical analysis revealed that there are no significant differences among the fragmentation rates and also in Pre-embryo Genome Activation (EGA) and Embryo Genome Activation (EGA) phases. This study would be beneficial in terms of controlling the DNA repair gene activity during the pre-implantation phase. The expression of BRCA1 could be a useful health assessment indicator for embryos.